2012
DOI: 10.3892/ijo.2012.1549
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous siRNA-mediated knockdown of antiapoptotic BCL2, Bcl-xL, XIAP and survivin in bladder cancer cells

Abstract: Bladder cancer (BCa) represents the ninth most common malignancy worldwide. Despite intensive treatment with surgery and chemotherapy the prognosis for BCa patients particularly at advanced stages is poor. The ability to evade apoptosis is a hallmark of cancer cells. Since the antiapoptotic genes BCL2, Bcl-xL, XIAP and survivin are frequently upregulated in BCa tissues, their combined siRNA-mediated knockdown might be more potent in decreasing BCa growth than the single inhibition of one target. Against each t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Additionally, p53 has been previously indicated to transcriptionally activate Bax expression (25). The abnormal expression of the Bcl-2 and Bax proteins in bladder cancer has been previously illustrated (26,27). The results of the present study indicated an increased Bax/Bcl-2 ratio due to oxymatrine, which indicates that a p53-Bax dependent mechanism may be involved in this process.…”
Section: Discussionsupporting
confidence: 63%
“…Additionally, p53 has been previously indicated to transcriptionally activate Bax expression (25). The abnormal expression of the Bcl-2 and Bax proteins in bladder cancer has been previously illustrated (26,27). The results of the present study indicated an increased Bax/Bcl-2 ratio due to oxymatrine, which indicates that a p53-Bax dependent mechanism may be involved in this process.…”
Section: Discussionsupporting
confidence: 63%
“…54 by which that the maintenance of high p53 levels was deemed as a prerequisite for inducing cell apoptosis. However, this study could not be directed comparatively with that report as we had deliberately suppress three proteins in a simultaneous fashion although it is important to note that this was not the first time that this simultaneous repression of multiple protein target was attempted 55, 56 . Nonetheless the general consensus was that multiple protein suppression in a concurrent fashion could indeed shortened the time-line required for apoptosis (24 hours) 56–58 and our findings here were no different.
Figure 5( A ) Levels of suppression of Survivin and expression of p53 for 2 h, 4 h and 8 h for MBA-MD 231 cells.
…”
Section: Resultsmentioning
confidence: 98%
“…Inhibition of the Akt/NF-κB pathways results in the downregulation of Bcl-2 with a simultaneous upregulation of caspase-3 (20,22,25). In the present study, ursolic acid was used to treat T24 bladder cancer cells.…”
Section: Discussionmentioning
confidence: 98%